Support System for Semiautomatic Quantification of Pulmonary Fibrosis in CT Images - Rodríguez Obregón, D. E.; Mejía Rodríguez, A. R.; Dorantes Méndez, G.; Arce Santana, E. R.; Charleston Villalobos, S.; Mejía Ávila, M.; Mateos Toledo, H.; González Camarena, R.; Aljama Corrales, A. T. (Revista Mexicana de Ingenieria Biomedica, 2017)
A method to estimate the pulmonary fibrosis in computed tomography (CT) imaging is presented. A semi-automatic segmentation algorithm based on the Chan-Vese method was used. The proposed method shows a similar fibrosis region with respect to clinical expert. However, the results need to be validated in a bigger data base. The proposed method approximates a fibrosis percentage that allows to achieve this procedure easily in order to support its implementation in the clinical practice minimizing the clinical expert subjectivity and generating a quantitative estimation of fibrosis region.